1991
DOI: 10.1148/radiology.180.3.1714611
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinomas with excessive copper accumulation: CT and MR findings.

Abstract: Results of orcein staining and findings obtained with non-contrast-medium-enhanced computed tomography (CT) and magnetic resonance (MR) imaging (T1- and T2-weighted images) were compared for 53 histologically confirmed hepatocellular carcinomas (HCCs). HCCs were 5 cm in the largest diameter. Three lesions with diffuse and strong orcein staining were highly attenuating on nonenhanced CT images. Electron x-ray microanalysis of one of them revealed copper. The high attenuation value at nonenhanced CT may have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…Although few, however, there were several non-FNH nodules that showed high signal intensity on HBP. High signal intensity of one hypovascular hepatocellular nodule may be attributable to high signal intensity on precontrast T1-weighted image, which are sometimes observed in dysplatic nodules or early HCC, due to cooper or iron deposition [12][13][14] (Fig.2) or fatty metamorphosis [15]. Because EOB uptake have been reported to be almost constant regardless of the grade of HCC, if the precontrast signal intensity is high, that would be directly reflected on the SI on HBP [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although few, however, there were several non-FNH nodules that showed high signal intensity on HBP. High signal intensity of one hypovascular hepatocellular nodule may be attributable to high signal intensity on precontrast T1-weighted image, which are sometimes observed in dysplatic nodules or early HCC, due to cooper or iron deposition [12][13][14] (Fig.2) or fatty metamorphosis [15]. Because EOB uptake have been reported to be almost constant regardless of the grade of HCC, if the precontrast signal intensity is high, that would be directly reflected on the SI on HBP [16].…”
Section: Discussionmentioning
confidence: 99%
“…In the early stages of multistep hepatocarcinogenesis [12,13], some hepatocelllar nodules including regenerative nodules (RN), dysplastic nodules (DN), early hepatocellular carcinomas (eHCC) or well differentiated hepatocellular carcinomas (wHCC), have been known to exhibit high signal intensity on T1WI, either related or unrelated to fatty metamorphosis [14][15][16][17]. Therefore, there could be a hypothesis that signal intensity before contrast administration may influence signal intensity on the postcontrast image.…”
Section: Assessmentmentioning
confidence: 99%
“…As for HCC, excessive Cu accumulation has been noticed in the human HCC samples. 28,29 No studies, however, have been performed to examine the effect of Cu on HCC development, except for a study on the Long-Evans Cinnamon (LEC) rat model of Wilson's disease. 42,43 LEC rat is a mutant strain, which consistently developed hepatitis and HCC.…”
Section: Discussionmentioning
confidence: 99%
“…21,28 Regarding HCC, it has been reported that excessive Cu level was found in the human HCC tissue as compared to the non-HCC regions. 28,29 In the present study, to elucidate the role of Cu and the feasibility of Cu-chelating agents in the future clinical applications, we examined the effect of the Cu-chelating agents, penicillamine and trientine, on tumor development and angiogenesis in the murine xenograft HCC model.…”
mentioning
confidence: 99%
“…The former type is diamagnetic and does not have unpaired electrons (17); therefore, it does not influence the MR signal unless extremely high concentrations are achieved (18). Divalent copper is paramagnetic and decreases T1 and T2 relaxation rates, an effect due to one unpaired electron (17).…”
Section: Coppermentioning
confidence: 99%